Exploring the Impact of Leadership Styles on Organizational Innovation of Business Selected Enterprises in the 2nd District of Albay - Mariñas, Mercy (JPAIR Multidisciplinary Research, 2025)
In today’s fast-paced business world, leaders significantly influence organizational culture and performance, promoting creativity, experimentation, and risk-taking. Understanding leadership styles can help organizations create a culture that supports idea generation and long-term success. This descriptive-quantitative research explores the impact of leadership styles on the organizational innovation of business enterprises in the 2nd District of Albay. Specifically, it determines the status of business establishments in terms of number of employees, kinds of business, years of existence, types of business operation, and others, whether franchise, outsourcing, and branches; identify the types of leadership styles in terms of planning, organizing, leading, and controlling; determine the challenges encountered on the leadership styles towards organizational innovation in business establishment along the aforementioned variables; and propose leadership style framework on organizational innovation for business enterprises. Survey questionnaires were distributed to 36 business establishments and answered by managers and employees. Based on the results, the 2nd district of Albay has a stable economic environment, with 53% of establishments having over 500 employees, 69% having over 20 years, and 72% being corporations. Leadership styles, such as visionary, supportive, and coaching, influence business operations. The Leadership Styles Framework on Organizational Innovation emphasizes flexibility, collaborative decision-making, cultural sensitivity, community involvement, innovation metrics, agile team structures, and learning initiatives.